Diurnal Bettles Around Universitas Muhammadiyah Palembang - Sri Wahyuni Sumah, Astrid; Kusumadinata, Ali Alamsyah (AGRINUS : Jurnal Agro Marin Nusantara, 2024)
The existence of beetles depends on the availability of energy and food sources to survive and carry out activities. The diversity of beetles in a habitat can be influenced by other factors, apart from energy and food sources. These factors include land use type, seasonal differences and habitat fragmentation. Regional differences and land use types may not always influence beetle diversity. However, changes in land use can affect the presence and diversity of beetles. So, this research aims to determine the diversity of diurnal beetles around the Muhammadiyah University Palembang campus. Diurnal beetle collection was carried out by purposive sampling using pitfall traps and direct collection at five observation points. The research results showed that 76 individuals from 7 species of diurnal beetles were identified as belonging to the order Coleoptera. The Coccinella transversalis beetle (family Coccinellidae) was the most beetle species found (36 individuals) and the beetle Bradycellus nigrinus (family Carabidae) was the fewest beetle species (2 individuals) found. The impact of changes in land use affects the species richness of diurnal beetles and also impacts the growth of previously different plant vegetation. However, the distribution of diurnal beetle species shows an even distribution and there is no dominant species. Keywords: Number of species, diversity, richness, diurnal beetles